EFFECT OF SOME PLANT EXTRCT, CALICUM CHLORIDE AND STORAGE METHOD INQUALITIES AND MARKETING OF THE APRICOTFRUITS ,3ZAGAINAA (2) CHEMICAL CHARACTERISTICS - Burhan, Marwa Hadi; AL-Shemmery , Ghalib Naser (Diyala Agricultural Sciences Journal, 2013)
The study was conducted in the laboratory of Department of Horticulture and Landscape on the fruits of apricot class (Zagainah 3). The fruits stored at refrigerated store's and evaporative In the store of the Department of Horticulture ,College of Agriculture - Tikrit University for two seasons, 2008 – 2009 .Fruits taken from a 7-year-old trees from a private orchard near the city of Baiji ,3/4 fruits collar after 79 days after full plum at 20/5 ,22/5/ 2009. Fruits dipping in extract, Okra 75% concentration 20 mints, pomogranatium 8%con. 5 mints, Sider leaves 75% con. 20 mints andCalciumChloride 5% con. The control treatment of fruits divided tow parts, the first storage at cold storage at 4 o ±1o and 80-85% temperature, another storage at ventilation storage. The fruits package at poly ethylene 5kg. The Result were: 1- Calcium Chloride treatment has maintained the Totalacidity, TSS, and taste 2-fruits treatment with Okra extract maintained the TSS and test at second season. 3- Pomegranate peel extract maintained the acidity, high TSS, Carotenoid and test in bath storages. 4- Sider leaves extracts maintained a high TSS, total acidity, Carotenoid and excellentteats. 5- Control treatment reduce the TSS, carotenoid and maintained total sugar.